JUDICIAL LIMITS OF INTERVENTION IN ADMINISTRATIVE COURT - Prasetyo Nugroho; Shinta Hadiyantina; Sudarsono (CV. RADJA PUBLIKA, 2025)
This journal aims to analyze the intervention process in dispute resolution in the Administrative Court. This study identifies two main problems: first, the mechanism for third-party entry into the dispute resolution process in the Administrative Court, and second, the legal consequences of third-party intervention in the case under study. The results of the study show that based on Article 83 of Law Number 5 of 1986 concerning Administrative Courts, third parties can enter the trial process during the examination, either on their own initiative, at the request of one of the parties, or at the initiative of the judge. The legal consequence of the entry of this third party is that they obtain the status of the Second Defendant of Intervention, which gives them the right to defend their interests in the trial process. This study emphasizes the importance of the presence of third parties in maintaining justice and legal certainty in state administrative disputes. The conclusion of this paper is that although intervention provides an opportunity for interested parties to participate in the legal process, there is a need for renewal and codification of the code of procedure in the Administrative Court to be more responsive to the dynamics of existing dispute resolution.